0071 Perineuronal Nets In The Thalamic Reticular Nucleus Regulate Neuronal Excitability And Gate Coupling Of Sleep Spindles To Cortical Slow Waves. (27th April 2018) - McKenna, J T; Yang, C; Katsuki, F; Strecker, R E; Basheer, R; McNally, J M; Brown, R E
Abstract: Introduction: Thalamic reticular nucleus (TRN) GABAergic neurons generate sleep spindles. Most TRN neurons express the calcium-binding protein, parvalbumin (PV), and many are surrounded by extracellular matrix complexes called perineuronal nets (PNNs). A recent study reported marked post-mortem reductions of TRN PNNs and PV expression in patients with schizophrenia or bipolar disorder. However, the functional effects of diminished TRN PNNs are unclear. Here, we investigated the effects of enzymatic degradation of PNNs in TRN on neuronal excitability in vitro and sleep EEG oscillations in vivo . Methods: Chondroitinase ABC (ChABC), an enzyme that degrades PNNs, was injected into TRN, to knockdown PNNs. Wisteria Floribunda Agglutinin (WFA) immunolabeling was used to identify PNNs. In vitro recordings were performed in slices from PV-tdTomato mice to examine the excitability of TRN PV neurons. ChABC injections and EEG/EMG recordings in vivo were used to evaluate the effect on sleep oscillations and their coupling. Results: PV/WFA co-localization in TRN was decreased by 71% (1d, N=2), 68% (3d, N=2) and 24% (7d, N=1) after ChABC injections. The ability of TRN PV neurons to maintain high-frequency discharge in response to current injection was impaired 2-3d after ChABC injection (N=2), compared to those without ChABC injection (N=2). Initial EEG recordings in one mouse revealed spindles were more likely to be coupled to the upstate of the cortical slow wave (non-uniform distribution and a common phase direction, Rayleigh test) pre-injection, whereas post-injection there was no preferred phase, indicating impaired coupling of spindles with slow waves. Conclusion: Degradation of PNNs impairs the ability of TRN neurons to maintain the high frequency discharge required to generate sleep spindles and attenuates NREM spindle/slow wave coupling. TRN PNNs abnormalities may impair the coupling of spindles to slow waves required for sleep-dependent memory consolidation in patients with schizophrenia or bipolar disorder. Support (If Any): VA Merits I01BX001404, 1I01BX001356, 1I01BX002774; VA CDA IK2BX002130; NIMH MH039683 and MH107650. JTM received partial salary compensation and funding from Merck MISP, but has no conflict of interest with this work.